2011
DOI: 10.1073/pnas.1106999108
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric vs. spontaneous exit-site (E-site) tRNA dissociation early in protein synthesis

Abstract: During protein synthesis, deacylated transfer RNAs leave the ribosome via an exit (E) site after mRNA translocation. How the ribosome regulates tRNA dissociation and whether functional linkages between the aminoacyl (A) and E sites modulate the dynamics of protein synthesis have long been debated. Using single molecule fluorescence resonance energy transfer experiments, we find that, during early cycles of protein elongation, tRNAs are often held in the E site until being allosterically released when the next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 58 publications
4
55
1
Order By: Relevance
“…However, the experimental findings of Nierhaus and his coworkers [46]- [50] described above have recently been refused to accept by many research groups [51]- [54]. Chen et al [53] analysed how E-site tRNA is dissociated early in protein synthesis. They denoted the two options as the 2-3-2 tRNA and 2-1-2 tRNA pathways, where the integers indicate the number of tRNAs occupying the ribosome during the conversion of the POST complex to the PRE complex.…”
Section: Negative Cooperativity Between a And E Sitesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the experimental findings of Nierhaus and his coworkers [46]- [50] described above have recently been refused to accept by many research groups [51]- [54]. Chen et al [53] analysed how E-site tRNA is dissociated early in protein synthesis. They denoted the two options as the 2-3-2 tRNA and 2-1-2 tRNA pathways, where the integers indicate the number of tRNAs occupying the ribosome during the conversion of the POST complex to the PRE complex.…”
Section: Negative Cooperativity Between a And E Sitesmentioning
confidence: 99%
“…Petropoulos and Green [54] used the same buffer, and yet refused the negative cooperativity between A-and E sites [46]. Chen et al [53] observed that the 2-3-2 pathway only occurred shortly after initiation and followed by consecutive 2-1-2 pathways and that the translation pathway is mainly determined by the PRE conformational states (either classical or hybrid). They used TAM 15 buffer, which contains 15 mMol MgAc 2 [53].…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the early rounds of elongation were recently examined using smFRET, and this uncovered an additional pathway of tRNA release that was not observed in later rounds of elongation 61 . In this pathway, the deacylated tRNA remains associated with the ribosomal E-site until the next charged tRNA binds to the A-site, at which point the deacylated tRNA is ejected from the E-site.…”
Section: Photoswitchable Fluorescent Probesmentioning
confidence: 99%